Konsep-Konsep Matematika pada Alat Musik Tradisional Indonesia dalam Perspektif Etnomatematika - S. Pt. Oka Pradnya Pratama; Putu Kartika Dewi; Gede Suweken; Gst. Ayu Mahayukti; I Made Ardana (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Ethnomathematics is a field of study that connects mathematical concepts with cultural practices and has the potential to serve as a contextual approach to learning. Traditional musical instruments, as cultural heritage, embody various mathematical concepts that can enrich educational practices. This study aims to identify and analyze ethnomathematical concepts embedded in traditional musical instruments through a Systematic Literature Review (SLR). Following the established inclusion criteria, 11 scholarly articles were selected and synthesized. The findings show that geometric concepts, particularly circles, cylinders, and cones, are the most frequently identified in the structures of traditional musical instruments. Other concepts include arithmetic sequences, number patterns, mathematical modeling, and mathematical relationships reflected in rhythmic patterns. These findings indicate that traditional musical instruments contain diverse mathematical structures with strong potential for contextual and meaningful mathematics learning. However, most existing studies remain exploratory and descriptive. This review provides a comprehensive synthesis of ethnomathematical concepts in traditional musical instruments while highlighting opportunities for future research on their effectiveness in mathematics education.